International protection from unconventional weapons - Aljasmi, Nouf (Journal of Legal Sciences, 2023)
War is one of the phenomena accompanying the human race since ancient times, so we find that the human element has mastered the use manufacture of weapons and worked on their development in order to provide means of protection and prevention from any external aggression by the enemies. The rapid developments on those weapons has led to an increase in their danger, Therefore, we find that the world limits their use production and that’s why many treaties have been concluded to dismantle them and limit their spread, and to preserve the security and stability of countries from the negative damages resulting from non-conventional weapons. From this standpoint, there are many existing international efforts to prevent the spread of non-conventional weapons in all its forms, to maintain international peace and security. In this research we will discuss the definition of weapons and their types, the upbringing and developments that man has gone through in the manufacture of unconventional weapons, and how man has harnessed natural materials and used them in non-human industries, and how he made them with his use of what has been invented of modern technology and applications in harming the human race not only, But also in harming all living creatures on the surface of the earth, as well as the environment around it, and finally methods of protection and prevention from these unconventional weapons.